Secretory Leucoprotease Inhibitor Impairs Toll-Like Receptor 2- and 4-Mediated Responses in Monocytic Cells - Greene, Catherine M. (American Society for Microbiology, 2004)
Secretory leucoprotease inhibitor (SLPI) is an anti-inflammatory antiprotease which can inhibit lipopolysaccharide-induced NF-κB activation. We examined its ability to inhibit NF-κB activation induced by lipoteichoic acid and investigated the effects of oxidation or complex formation with neutrophil elastase on SLPI's anti-inflammatory properties in U937 myelomonocytic cells and macrophages.